Experimental results of a solar space heating system with PCM: Small-scale setup and real-scale setup. (2022) - Agrawal, Nidhi; Kumar, Bhuvnesh; Verma, Bhanu; Mehling, Harald; Arora, Bharti
Highlights: ETC has been modified to an air collector which helps reducing the heat losses. Thermal energy storage has been used to heat the room during off-sunshine hours. Comparison of different phase change materials has been shared. 29 degree phase change material has been chosen as the best PCM to maintain the temperature in the desired range. Abstract: Northern India receives considerable solar energy, while at the same time has a large demand for space heating. Solar space heating, combined with a thermal energy storage using PCM, could play a very important role in maintaining comfort conditions i.e. 15 ℃ to 20 ℃ in the cold regions where the temperature goes down to −15 ℃ to −20 ℃. This paper presents experimental results for using PCMs with transition temperature 22 ℃, 29 ℃, and 34 ℃, used for maintaining the comfort conditions, tested in a small-scale setup and a real-scale setup. The results show stabilization of the temperature of the test room, PCM type, and required PCM quantity.